Effects of secondary release of chromium and vanadium on soil properties, nutrient cycling and bacterial communities in contaminated acidic paddy soil. (15th January 2023) - Peng, Dinghua; Zhang, Renfeng; Chen, Yahui; Jiang, Lili; Lei, Ling; Xu, Heng; Feng, Su
Abstract: Although the contamination situation of chromium (Cr) and vanadium (V) have been revealed, the effects of their re-release on ecological risk in contaminated acidic paddy soil are unclear. To evaluate the effects, we assigned soil microcosms across three different concentration (100, 200, 300 mg/L) and introduced Cr and V alone or combination into an already slightly contaminated acidic soil. We found that Cr and V alone or interacted to increased soil bioavailable-metals, changed soil properties and nutrients to varying degrees. Meanwhile, soil ammoniacal nitrogen (NH4 + -N) and nitrate nitrogen (NO3 − -N) contents, nitrogen (N) -cycling enzyme activities, microbial mass N were significantly influenced by Cr addition. Which demonstrated that Cr re-release may disturb soil N cycle. However, V alone significantly improved soil NO3 − -N contents, cellulase and dehydrogenase activities, soil respiration intensity and microbial mass carbon: nitrogen. Meanwhile, V addition also decreased bacterial diversity while Cr addition increased bacterial diversity and shaped new bacterial community, some V(V) and Cr (VI) reducing bacteria were identified. Heatmap of Pearson correlation and Redundancy analysis showed that NH4 + -N, NO3 − -N, Potassium, Phosphorus, and Cr played an important role in bacterial community structure. These findings suggested that re-release of Cr and V disturbed soil function and raised ecological risks, and the power to destroy the ecosystem stability originated from Cr was much stronger than V. This study was contributed to understand the effects of Cr and V re-release on microecology in contaminated acidic agricultural soil. Graphical abstract: Image 1 Highlights: Effect of Cr and V re-release on acidic soil microecosystem were fully evaluated. Addition of Cr alone or jointly with V disturbed soil N cycling but not C cycling. Cr addition increased bacterial diversity and shaped new bacterial community. Re-release had not impact on soil microbial biomass and bacterial communities.